A nationwide cohort study of the incidence of inflammatory bowel disease in Sweden from 1990 to 2014. Issue 6 (14th December 2021) - Forss, Anders; Clements, Mark; Bergman, David; Roelstraete, Bjorn; Kaplan, Gilaad G.; Myrelid, Pär; Halfvarson, Jonas; Olén, Ola; Ludvigsson, Jonas F.
Summary: Background: Epidemiological studies have shown inconsistent incidence rates (IRs) for inflammatory bowel disease (IBD). Aim: To assess the incidence and temporal trends of IBD in Sweden. Methods: Nationwide cohort study based on diagnostic codes for IBD and biopsy reports registered through the ESPRESSO cohort in 1990‐2014. Age‐specific and age‐standardised IRs and cumulative incidence were calculated. Results: Overall, we identified 65 908 cases of incident IBD: ulcerative colitis (UC, n = 38 261, 58%), Crohn's disease (CD, n = 18 577, 28%) and IBD‐U (n = 9070, 14%). During 1990‐2014, the overall IRs per 100 000 person‐years were 29.0 (95% CI: 27.3‐30.7) for IBD, 16.9 (15.9‐17.9) for UC, and 8.1 (7.7‐8.6) for CD. For IBD‐U, the IR was 5.2 (4.9‐5.6) in 2002‐2014. The annual incidence of IBD, UC and CD increased by approximately 7% per year between 1990 and 2001 ( P < 0.001) and then decreased by 1%‐2% per year from 2002 onwards ( P < 0.001). IRs for IBD, UC and IBD‐U were higher in males while the IR for CD was higher in females. The lifetime risk of IBD was about 2.5% for both sexes. Conclusions: In Sweden, the incidence of IBD in all subtypes increased in 1990‐2001 but has since declined. One in 40 individuals is expected to be diagnosed with IBD during their lifetime. Abstract : A nationwide cohort study of the incidence of inflammatory bowel disease in Sweden from 1990 to 2014.